Obstacless to applying Actuarial Accounting,"An applied study on insurance companies in the city of Benghazi" - عمر بشير فشتول, أحمد (Dirasat in Economics and Business, 2024)
This study aimed to identify the obstacles that hinder the application of actuarial accounting in insurance companies in the city of Benghazi, The obstacles were divided into administrative obstacles, human obstacles, and technical obstacles. To achieve the goal of the study, the study adopted the deductive-inductive approach. The study also relied on the questionnaire form as the main tool for collecting data, The study population was represented by the executive management of insurance companies operating in the city of Benghazi, represented by department directors and department heads. A random stratified sample was also selected from the study population, The size of the selected or distributed sample was 68 individuals. Questionnaire forms were distributed to the entire study sample. 52 valid questionnaires were retrieved for analysis, or approximately 76%. The study used statistical methods represented in descriptive statistics methods, represented by arithmetic means, standard deviation, and frequency ratios, were also used. Inferential statistics method, represented by the one-sample t-test, was used to test the study hypotheses, The results of the study concluded that there are obstacles (administrative obstacles - human obstacles - technical obstacles) that prevent the application of actuarial accounting in insurance companies in the city of Benghazi, The study also recommended many recommendations, perhaps the most important of which is working to develop a database that includes information on the demographic environment of subscribers to insurance companies and establishing a department or section that works on preparing actuarial operations, and also working to prepare scientifically and professionally qualified human cadres to carry out actuarial work. The study recommended the necessity of insurance companies working to increase awareness among their employees of the importance of applying actuarial accounting, as well as working to evaluate the financial risks of insurance products in an actuarial manner for the company’s income Obstacless, Actuarial Accounting, Insurance Companies.